Production of methane from palm oil mill effluent using membrane anaerobic system - Singanathan, Jayabalan (2010)
Palm oil mill effluent (POME) is a highly polluting wastewater that pollutes the environment if discharged directly due to its high chemical oxygen demand (COD), total suspended solids (TSS), volatile suspended solids (V•SS) and biological oxygen demand (BOD). The transformation of the palm oil mill effluent POME) to methane gas by membrane anaerobic system (MAS) was evaluated. The membrane used in the system is a cross flow ultra filtration membrane (UF). The untreated water or the retentate was recycled back into the anaerobic reactor. 20 liter of raw material cif-palm oil mill effluent (POME) were used and the-PH, biological oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS) and volatile suspended solids (VSS) are determined before and after the anaerobic digestion. There is a huge decrease in value of BOD, COD, TS and VSS in permeate compared to the POME from the reactor before and after the treatment. The BOD of permeate on the 7th day is 612 mgIL whereas the COD is 320 mg/L. The pH of the POME inside the reactor is maintained in from 6.5 to 7.5 to induce rnethanbgenic reaction, instead of acidogenic reaction. About 86% of methane gas released during the anaerobic digestion.